The peptidoglycan-associated lipoprotein gene mutant elicits robust immunological defense in mice against Salmonella enteritidis - Zhao, Guixin; Duan, Wenlong; Zhang, Lu; Sun, Wenchao; Liu, Wan; Zhang, Xiaoyu; Zhang, Yanying; Shi, Qiumei; Wu, Tonglei (Frontiers in Microbiology, 2024)
Background: Salmonella enteritidis (S.enteritidis ), a zoonotic pathogen with a broad host range, presents a substantial threat to global public health safety. Vaccination stands as an effective strategy for the prevention and control of S.enteritidis infection, highlighting an immediate clinical need for the creation of safe and efficient attenuated live vaccines.Methods：In this study, a S.enteritidis peptidoglycan-associated lipoprotein (pal) gene deletion strain (Δpal), was constructed. To assess its virulence, we conducted experiments on biofilm formation capability, motility, as well as cell and mouse infection.Subsequently, we evaluated the immune-protective effect of Δpal.: It was discovered that deletion of the pal gene reduced the biofilm formation capability and motility of S.enteritidis. Cell infection experiments revealed that the Δpal strain exhibited significantly decreased abilities in invasion, adhesion, and intracellular survival, with downregulation of virulence gene expression, including mgtC, invH, spvB, sipA, sipB, ssaV, csgA, and pipB. Mouse infection experiments showed that the LD50 of Δpal increased by 10 4 times, and its colonization ability in mouse tissue organs was significantly reduced. The results indicated that the pal gene severely affected the virulence of S.enteritidis. Further, immunogenicity evaluation of Δpal showed a significant enhancement in the lymphocyte transformation proliferation capability of immunized mice, producing high titers of specific IgG and IgA, suggesting that Δpal possesses good immunogenicity. Challenge protection tests demonstrated that the strain could provide 100% immune protection against wild-type strains in mice.Discussion: This study proves that the pal gene influences the virulence of S.enteritidis, and Δpal could serve as a candidate strain for attenuated live vaccines, laying the foundation for the development of attenuated live vaccines against Salmonella.